0721 Pediatric Spina Bifida and Sleep Disordered Breathing: Should PSG be Routine?. (12th April 2019) - Maddox, Mary H; Hopson, Betsy; Blount, Jeffrey; Arynchyna, Anastasia; Rocque, Brandon
Abstract: Introduction: Data documenting sleep disordered breathing (SDB) in the pediatric myelomeningocele (MMC) population is limited. We sought to prospectively explore SDB in patients with MMC and Chiari II malformation by referring a cohort of patients seen from 3/2016-12/2018 in a multidisciplinary MMC clinic for polysomnography (PSG). Methods: Out of 348 MMC patients followed in a multi-disciplinary clinic, we screened a cohort of 86 patients with routine PSG regardless of symptoms or clinical concerns for SDB. None of the patients had undergone previous PSG. We assessed age, gender, hydrocephalus, shunt status, functional level of lesion (FLOL), apnea/hypopnea index (AHI), and type of apnea, if present. Descriptive analysis used frequency counts, mean, and median to look at rate of apnea. Odds ratio (OR) and confidence interval (CI) assessed if any variables were predictive of SDB. Results: Out of the 86 patients, (43 male, 43 female), 90.7% had hydrocephalus, of whom 85.9% had a VP shunt, and 14.1% had ETV/CPC only. The age range was 0.83-21.082 years, mean 9 years. The AHI range was 0-23.2, mean 3.06. Overall, 57% had AHI>1.5 while 38.4% had AHI> 2.5. If the AHI> 2.5, the mean was 6.4 and median was 4.4. Type of apnea was divided into Obstructive (22.1%), Central/Combined (32.6%), and None (45.3%). Gender, age, hydrocephalus, and shunt status offered no predictive value, however, more rostral FLOL was associated with greater apnea. For AHI > 1.5, compared to sacral FLOL, OR at thoracic FLOL was 6.9 (p=0.027) and high lumber FLOL OR was 5.182 (p=0.032). For AHI >2.5, OR at thoracic FLOL was 7.5 (p=0.013) and high lumbar FLOL OR was 5.000 (p=0.034). Conclusion: The rate of SDB breathing in pediatric MMC patients is significantly higher than the reported rate of SDB in healthy patients, regardless of symptoms. With almost 40% of pediatric MMC patients demonstrating SDB on routine PSG, it may be important to consider PSG as part of the routine care of pediatric MMC patients, particularly in patients with thoracic and high lumbar FLOL. Support (If Any): none